Search for neutral supersymmetric Higgs bosons in pp collisions at sqrt[s] = 1.8TeV. - Affolder, T; Akimoto, H; Akopian, A; Albrow, MG; Amaral, P; Amendolia, SR; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Asakawa, T; et al. (2001)
We present the results of a search for neutral Higgs bosons produced in association with b quarks in pp-->bb(phi)-->bbb final states with 91+/-7 pb(-1) of pp collisions at sqrt[s] = 1.8 TeV recorded by the Collider Detector at Fermilab. We find no evidence of such a signal and the data are interpreted in the context of the neutral Higgs sector of the minimal supersymmetric extension of the standard model. With basic parameter choices for the supersymmetric scale and the stop-quark mixing, we derive 95% C.L. lower mass limits for neutral Higgs bosons for tan(beta) values in excess of 35.